Contingent Valuation of Woodland-Owner Private Amenities in Spain, Portugal, and California. - Campos, Pablo; Oviedo, Jose L; Caparros, Alejandro; Huntsinger, Lynn; Coelho, Inocencio (Rangeland Ecology & Management, 2009)
Most of the Mediterranean woodlands in Spain, Portugal, and California are managed as agrosilvopastoral enterprises, producing some combination of livestock, wood, cork products, and crops, as well as wildlife habitat and diverse environmental services. Private amenity benefits to landowners have been suggested as an explanation for high land prices and the persistence of such rangeland enterprises despite apparently marginal cash returns. In this study, private amenity values are estimated using a contingent valuation technique in surveys of private woodland owners as part of five case studies, using a design developed to separate landowner amenity income and capital values. Nonindustrial private landowners were asked about the maximum amount of money that they were willing to give up (to pay) before selling their property to invest in more commercially profitable assets, and the proportion of the market price of their woodland that they think is explained by privately consumed amenities. Amenity values were found to be relevant because, in all cases, landowners were willing to pay >€120 · ha−1 · yr−1, at 2002 prices, and attributed > 30% of land market price to amenities. These values represent an amenity profitability rate > 2% in all case studies. The data analysis shows some similarities, but mostly divergences, in the different land-simulated and amenity-simulated markets.
Keywords: agroforestry systems; environmental economics; environmental services; Mediterranean woodlands; private ownership; Stated Preferences